Síntese análise das propriedades magnéticas da ferrita de NiMg e características de absorção de radiação - Silva, José Eves Mendes da (2008)
It was synthesized different Ni1-xMgxFe2O4 (0,2 ≤ x ≤ 0,7) compositions by use of citrate precursor method. Initially, the precursory citrates of iron, nickel and magnesium were mixed and homogenized. The stoichiometric compositions were calcined from 350°C to 1200°C at ambient atmosphere or in argon atmosphere. The calcined powders were characterized by XRD, TGA/DTG, FTIR, magnetic measures and reflectivity using the wave guide method. I was observed pure magnetic phase formation between 350°C and 500°C, with formation of ferrite and hematite after 600°C at ambient atmosphere. The calcined powder at argon atmosphere formed pure ferromagnetic phase at 1100°C and 1200°C. The Rietveld analyses calculated the cations level occupation and the crystallite size. The analyses obtained nanometric crystals (11-66 nm), that at 900°C/3h presents micrometric sizes (0,45 - 0,70 Om). The better magnetization results were 54 Am2/Kg for x= 0,2 composition, calcined at 350°C/3h and 30 min, and 55,6 Am2/Kg for x= 0,2 1200°C, calcined in argon. The hysteresis shows characteristics of soft magnetic material. Two magnetization processes were considered, superparamagnetism at low temperature and the magnetic domains formation at high temperatures. The materials presented absorption less or equal the 50 % in ranges specific frequency. As for the 2,0 and 3,0 thickness (in 11,0 - 11,8 GHz), the reflectivity of the x= 0,3, 0,5 and 0,4 compositions, all calcined at 900°C/3h showed agreement with MS and O. Various factors contribute for the final radiation absortion effect, such as, the particle size, the magnetization and the polymer characteristics in the MARE composition. The samples that presented better magnetization does not obtaining high radiation absorption. It is not clear the interrelaction between the magnetization and the radiation absorption in the strip of frequencies studied (8,2 - 12,4 GHz)